Recent advances in the shape and configuration of photovoltaic thermal absorbers. Issue 2 (1st June 2023) - Kumar Tyagi, Praveen; Arora, Gaurav; Kumar, Rajan; Ali, Hafiz Muhammad; Rathore, Pushpendra Kumar Singh
ABSTRACT: Photovoltaic thermal (PVT) systems are solar systems with the primary goal of producing both heat and electricity. The geometrical design of PVT systems is an important aspect of energy production and, consequently, substantial research has been done to investigate the effect of different geometric configurations on the performance of PVT systems. Thus, the present paper provides a comprehensive review of the works that have explored the effects of various geometric channel configurations on the performance of PVT systems in terms of photovoltaic (PV) module temperature, thermal efficiency (ɳTh ), electrical efficiency (ɳEI ), and overall efficiency (ɳOv ). This review paper concluded that the geometry of the channel and flow channel configurations at the backside of the PV module are the most prominent factors to enhance the heat transfer rate. Most studies found that the optimal fluid flow channel configuration is the helical type, which provides good performance due to an increase in the heat transfer rate due to several bend sections that boost the heat transfer by disrupting the thermal boundary layer. Future research directions in this thrust area are also outlined in this review paper.